TEACHING RESOURCES OF TECHNICAL TEACHERS AT PRIMARY SCHOOLS IN THE SLOVAK REPUBLIC - LUKACOVA, Danka; BANESZ, Gabriel; VRANAKOVA, Zuzana (Trends in education, 2021)
The basic pillars of primary school teachers in teaching are the content and performance standards of subjects and teaching resources of individual subjects. The availability of textbooks in Slovakia has lagged behind in recent years, and teachers are announcing their lack for pupils. The subject of technology has undergone fundamental content changes since 2015, which require their reflection in new textbooks and workbooks. The aim of this paper is to evaluate the availability of learning resources for the subject of technology with a focus on electronic learning resources. A questionnaire of our own design was used for the research, which was sent to 110 primary schools with a return of 46 %. The results of the questionnaire were processed by methods of descriptive statistics. It has been found that print textbooks are on the verge of interest as a source of professional information, and teachers prefer electronic learning resources.
Keywords: textbooks; electronic resources; teachers; questionnaire